Length-weight relationship and condition factor of Gudusia chapra (Hamilton, 1822) from Panchet Reservoir, Jharkhand, India - Kumari, Suman; Sandhya, K. M.; Karnatak, Gunjan; ., Lianthuamluaia; Sarkar, U. K.; Panda, D.; Mishal, P. (Indian Journal of Fisheries, 2019)
This study provides length-weight relationship and condition factor (K) of Indian river shad Gudusia chapra (Hamilton, 1822) collected from Panchet Reservoir, Jharkhand, India during October 2014 to September 2015 using gillnets and drag nets. About 342 specimens (153 male and 189 female) of length range 4.7 to 15.1cm were collected. Length-weight relationship for male and female were calculated separately. The difference between the sexes was insignificant (independent t-test, p>0.05). The pooled length-weight regression equation was estimated as log W=-1.863+2.855 log L (r=0.983) which indicated negative allometric growth. The value of condition factor (Kn value) was observed to be nearer to or greater than one in both sexes, indicative of the general wellbeing of the fish in the Panchet Reservoir. This is the first report on length-weight relationship parameters of G. chapra from an Indian reservoir. Keywords: Allometric growth, Condition factor, Gudusia chapra, Length-weight relationship, Panchet Reservoir